Advancing Sustainable Construction in Nigeria: A Critical Review of Progress, Challenges, and Future Direction - Unegbu, Hyginus Chidiebere Onyekachi; Yawas, Danjuma S.; Dan-asabe, Bashar; Alabi, Abdulmumin Akoredeley (Jurnal Pengabdian KOLABORATIF, 2025)
This literature review examines the progress, challenges, and opportunities in adopting sustainable construction practices in Nigeria over the past two decades. Significant advancements have been made, particularly in the use of energy-efficient materials and Building Information Modeling (BIM), which have improved project efficiency and sustainability. Policy frameworks have evolved to support these technological innovations, but widespread adoption of sustainable practices is still hindered by economic constraints, cultural resistance, and regulatory gaps. Economic challenges, especially the high costs of sustainable technologies, are major obstacles, worsened by limited financial incentives and economic instability. Cultural factors, such as a preference for traditional construction methods, and inconsistent enforcement of building codes further complicate efforts to promote sustainability. Despite these barriers, there is growing awareness of the need to integrate sustainability into the construction sector, driven by both global environmental concerns and local development needs. The review also highlights its limitations, including a reliance on published academic literature, which may not fully capture recent industry trends or local realities. Excluding grey literature and non-English publications may omit important regional perspectives. The review recommends future research on detailed economic analyses of sustainable technologies, exploring the integration of traditional and modern practices, and comparative studies with similar countries.
Keywords: cultural resistance; economic constraints; green technologies; policy development; sustainable construction